2008
DOI: 10.1007/s12298-008-0008-0
|View full text |Cite
|
Sign up to set email alerts
|

Sucrose non-fermenting 1-related protein kinase 2 (SnRK2): a family of protein kinases involved in hyperosmotic stress signaling

Abstract: Our understanding of plant adaptation to abiotic stresses, which include drought, salinity, non-optimal temperatures and poor soil nutrition, is limited, although significant strides have been made in identifying some of the gene players and signaling partners. Several protein kinases get activated in plants in response to osmotic stress and the stress hormone abscisic acid (ABA). Among these is a superfamily of sucrose non-fermenting protein kinase genes (SnRK2). This review focuses on the developments relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 91 publications
0
10
0
Order By: Relevance
“…The SnRK2 family has been suggested to have evolved specifically for hyperosmotic stress signaling (Boudsocq et al, 2004;Umezawa et al, 2004;Kobayashi et al, 2005;Fujii et al, 2007;Shukla and Mattoo, 2008;Fujita et al, 2009). For example, Kobayashi et al (2005) identified 10 SnRK2 protein kinases encoded in rice (Oryza sativa), and all of these SnRK2s were specifically activated by osmotic stress at both the transcriptional and the posttranscriptional levels.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The SnRK2 family has been suggested to have evolved specifically for hyperosmotic stress signaling (Boudsocq et al, 2004;Umezawa et al, 2004;Kobayashi et al, 2005;Fujii et al, 2007;Shukla and Mattoo, 2008;Fujita et al, 2009). For example, Kobayashi et al (2005) identified 10 SnRK2 protein kinases encoded in rice (Oryza sativa), and all of these SnRK2s were specifically activated by osmotic stress at both the transcriptional and the posttranscriptional levels.…”
Section: Discussionmentioning
confidence: 99%
“…SUCROSE NONFERMENTING1-RELATED PROTEIN KINASES2 (SnRK2s) are a family of plant-specific protein kinases implicated in stress and abscisic acid (ABA) signaling (Yoshida et al, 2002;Boudsocq et al, 2004;Kobayashi et al, 2005;Umezawa et al, 2004;Fujii et al, 2007;Shukla and Mattoo, 2008;Fujita et al, 2009;Hirayama et al, 2010;Kulik et al, Figure 1. Phylogenetic analysis of SnRK2.6 proteins.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that cellular energy status plays a vital role in regulating litchi fruit senescence and browning [ 5 ]. As an energy regulator, snf1-related kinase 1 (SnRK1) has been reported to be involved in the global regulation of carbon and nitrogen metabolism, further affecting the cellular energy level [ 6 , 7 ]. Moreover, pathogen infection usually induces fruit senescence and browning.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, SnRK2 and SnRK3 are directly related to abscisic acid signal transduction [48]. Glyma.01G019400, Glyma.08G207900 and Glyma.08G273500 were annotated as indole-3-acetic acid-inducible genes; indole-3acetic acid is a ubiquitous endogenous auxin in plants.…”
Section: Candidate Gene Mining For Multiple-effect Qtlsmentioning
confidence: 99%